Dampak Pendidikan Inklusi terhadap Prestasi Akademik dan Keterampilan Sosial Siswa Berkebutuhan Khusus di SLB Negeri 2 Makassar - Sadriani, Andi (Peneliti.net, 2024)
This study aims to examine the impact of inclusive education on academic achievement and social skills of students with special needs at State Special School 2 Makassar City. Inclusive education is expected to provide equal learning opportunities for students with special needs, improve their academic achievement, and improve social skills in interacting with the environment. This study uses a qualitative approach involving 5 teachers and 3 parents of students as respondents. Data were collected through in-depth interviews, participatory observation, and document analysis, which were analyzed using thematic analysis techniques. The formulation of the problems studied include: (1) the impact of implementing inclusive education on the academic achievement of students with special needs, and (2) the impact of inclusive education on the social skills of students with special needs. The results of the study indicate that inclusive education has a positive effect on improving student academic achievement. With the support of adaptive learning, students with special needs show progress in basic academic skills such as reading and arithmetic. In addition, inclusive education helps students with special needs develop social skills, especially in interacting and communicating with peers. However, challenges in adjusting learning methods and managing differences in abilities still require special attention. Overall, inclusive education at State Special School 2 Makassar City provides positive benefits for students with special needs, both in academic and social aspects.